2014
DOI: 10.1021/ic4020702
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Phonon Properties, and Order–Disorder Transition in the Metal Formate Framework of [NH4][Mg(HCOO)3]

Abstract: We report the synthesis, crystal structure, thermal, dielectric, IR, and Raman studies of [NH4][Mg(HCOO)3] formate. Single-crystal X-ray diffraction shows that it crystallizes in the hexagonal space group P6322, with orientationally disordered NH4(+) ions located in the cages of the network. Upon cooling, [NH4][Mg(HCOO)3] undergoes a phase transition at around 255 K to the ferroelectric P63 structure. Raman and IR spectra show a strong increase in intensity of the N-H stretching bands as well as narrowing of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
172
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(191 citation statements)
references
References 30 publications
16
172
3
Order By: Relevance
“…The observation of the good dielectric hysteresis loop below T c confirmed that the low-temperature structure of these materials is ferroelectric [18]. It was also reported that the phase transition has an order disorder character [18][19][20]. Interestingly, X-ray diffraction data of Mg analog showed that ordering of NH 4 + cations occurs in two steps [19,20].…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…The observation of the good dielectric hysteresis loop below T c confirmed that the low-temperature structure of these materials is ferroelectric [18]. It was also reported that the phase transition has an order disorder character [18][19][20]. Interestingly, X-ray diffraction data of Mg analog showed that ordering of NH 4 + cations occurs in two steps [19,20].…”
Section: Introductionmentioning
confidence: 54%
“…They exhibit electric order at 191-255 K, associated with decrease of symmetry to P6 3 (C 6 6 ) [18][19][20]. The observation of the good dielectric hysteresis loop below T c confirmed that the low-temperature structure of these materials is ferroelectric [18].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…[17][18][19][20] It was proved by Xu, et al that the magnetic [NH 4 ][M(HCOO) 3 ] had electric ordering and could be a new type of MOF-based multiferroics. [21][22][23] The property of ferroelectricity induced by magnetic order was also found in the metal-organic framework magnet [CH 3 NH 3 ][Co(HCOO) 3 ]. 9,24 Recently, Ren-Gen Xiong and his team reported that the para-toferroelectricity occurred in range of 3 ] series, which the disorder-order transition of (CH 3 ) 2 NH 2 + template could be the origin of electric ordering.…”
Section: Introductionmentioning
confidence: 98%